Non-invasive estimation of left ventricular chamber stiffness using cardiovascular magnetic resonance and echocardiography - Ida Marie Hauge-Iversen; Einar S. Nordén; Arne Olav Melleby; Linn Espeland; Lili Zhang; Ivar Sjaastad; Emil Knut Stenersen Espe (Journal of Cardiovascular Magnetic Resonance)
Background: Preclinical studies exploring the underlying mechanisms of elevated left ventricular (LV) chamber stiffness play a crucial role in developing new therapeutic strategies. However, there is a lack of systematic evaluation of imaging biomarkers of diastolic function against gold standard assessment of LV chamber stiffness in rodents. Therefore, we aimed to evaluate imaging biomarkers of diastolic function from cardiovascular magnetic resonance (CMR) and echocardiography in predicting the slope of the end-diastolic pressure-volume relationship (EDPVR) in rats. Methods: Sprague Dawley rats with varying degrees of myocardial stiffness induced by aortic constriction (n=38) and healthy controls (n=9) underwent echocardiography and CMR at approximately 13 weeks post-operation. Imaging biomarkers of diastolic function were evaluated for their ability to predict the EDPVR slope from pressure-volume recordings using regression analysis and receiver operating characteristics analysis. Results: Both CMR and echocardiographic imaging biomarkers, in particular those related to the left atrium and mitral flow, were able to predict the EDPVR slope in a rat model with varying stiffness. From CMR, native T1 values, peak early diastolic longitudinal strain rate (SRe(long)) and E/SRe(long), left atrial (LA) ejection fraction, isovolumetric relaxation time (IVRT), E/A and peak LA strain, correlated best with the EDPVR slope (|r|=0.54–0.72). From echocardiography, E/A, E, LA diameter, e’/a’, E/SRe(long) and IVRT correlated with the EDPVR slope (|r|=0.49–0.67), while E/e’, e’ and E-wave deceleration time demonstrated poor correlation (|r|=0.17–0.27). Receiver operating characteristics analysis indicated better performance of CMR imaging biomarkers than echocardiography in predicting increased EDPVR slope. Conclusions: Several diastolic imaging biomarkers commonly employed in preclinical studies have poor ability to predict cardiac chamber stiffness. Our study identifies several imaging biomarkers obtained from both echocardiography and CMR that are able to estimate LV chamber stiffness non-invasively, providing an important tool for future mechanistic research on myocardial stiffness.